AB0036 Association between synovitis and inflammatory citokines serum levels in a cohort of patients affected by primary knee osteoarthritis. (15th June 2017) - Ceccarelli, F; Perricone, C; Pacucci, VA; Scirocco, C; Alessandri, C; Valesini, G; Conti, F
Abstract : Background: Osteoarthritis (OA) is characterized by progressive loss of cartilage, deterioration of subchondral bone and mild synovial inflammation. Classified for a long time as a non-inflammatory arthropathy, a growing number of evidences has suggested that OA course could be driven by systemic and localized inflammation. In particular, serum levels of Interleukin (IL)-6 have been associated with higher prevalence of osteophytes in older adults with knee OA. Furthermore, high levels of other inflammatory cytokines have been identified in serum and synovial fluid of OA patients. Objectives: In the present cross-sectional study, we aimed at analyzing the correlation between articular inflammatory state, reflected by ultrasonographically-detected synovitis, and the serum levels of 27 cytokines, chemokines and growth factors in a cohort of primary knee OA. Methods: We consecutively enrolled 47 patients (M/F 16/31, mean age ±SD 63.8±7.8 years, mean onset interval ±SD 70.0±78.6 months) affected by knees OA according to clinical and radiographic ACR criteria. Patients were excluded if they had received non-steroidal anti-inflammatory drugs or other analgesics within the 2 days before enrollment. Pain was assessed with a 100-mm visual analogue scale (VAS), and the Lequesne algo-functional index was used to measure the OA severity. BMI was registered. Each patient underwent ultrasonographic (US) assessment of both knees performed by a single operator. According with OMERACT definitions, we assessed the presence of synovial effusion, synovial hypertrophy and power Doppler. These elementary lesions were scored according to a semi-quantitative scale (0 = absent, 1 = mild, 2 = moderate and 3 = severe), the sum of them allows obtaining a total score of the patient's inflammatory state (0–18). Finally, blood samples for laboratory assays were obtained and commercially available multiplex bead based immunoassay kits (Human 27-plex, Bio-Rad laboratories, Hercules, CA) were used to measure concentrations of IL-1β, IL-1RA, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12, IL-13, IL-15, IL-17, FGF-Basic, G-CSF, GM-CSF, interferon-γ, IP-10, MCP-1, MIP-1α, MIP-1β, PDGF, RANTES, TNF, VEGF. Results: At the study enrollment, OA patients showed a mean±SD US synovitis score of 4.4±2.7, a mean±SD VAS pain rating of 53.3±16.6 mm (range 18–90 mm), a mean±SD Lequesne index of 10.2±4.2 (range 1.5–19), a mean±SD BMI of 26.8±4.2 (range 20–34.7). Positive correlations among US synovitis score and serum levels of IL-6 (r=0.3, p=0.01), IL-2 (r=0.3, p=0.01), IL-5 (r=0.3, p=0.01), IL-7 (r=0.3, p=0.03), MIP-1b (r=0.3, p=0.01), VEGF (r=0.3, p=0.02) were found. Moreover, US synovitis score positively correlated with Lequesne index (r=0.4, p=0.004) and BMI (r=0.4, p=0.04). Conclusions: The results of the present study confirmed that OA may be associated with systemic inflammatory changes, as demonstrated by the positive correlation between US synovitis and several inflammatory cytokines serum levels. Disclosure of Interest: None declared